Preparation method of OLED (Organic Light Emitting Diode) sealing slurry
OLED sealing slurry is prepared by configuring glass powders with different low melting points and adding composite powders with low expansion coefficient and light absorption fillers, which solves the problem of weak sealing and bonding strength, and achieves better packaging effect and device stability.
Patent Information
- Application Number
- CN202510314982.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-07-04
AI Technical Summary
The poor sealing and weak welding bonding of existing OLED packaging slurries lead to invasion of water vapor and oxygen, affecting the life and performance of the device.
By configuring the first and second low melting point glass powder and adding low expansion coefficient and light absorbing filler to the composite powder, the composite powder is formed to mix with the organic carrier, and an OLED sealing slurry is prepared to ensure that the thermal expansion coefficient matches and improve welding bonding force.
It improves the sealing properties and welding bonding force of the sealing slurry, reduces bubble residues during laser sealing, and ensures the stability and life of OLED devices.
Smart Images

Figure CN120247414A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the technical field of low-temperature sealing, and particularly relates to a preparation method of an OLED sealing paste. Background Art
[0002] In recent years, display technology has developed rapidly. As a highly potential display technology, OLED (Organic Light Emitting Diode) has shown unique advantages and been widely used in many fields. At the same time, OLED has excellent contrast, capable of presenting deep blacks and vivid colors, greatly enhancing the visual experience. It has a wide viewing angle, and the screen content can be clearly viewed almost from any angle. Moreover, its response speed is extremely fast, especially suitable for displaying dynamic images. For example, it has broad application prospects in many fields such as smartphones, high-definition TVs, wearable devices, and in-vehicle displays, and has become one of the hotspots in the current research and development of the display technology field.
[0003] However, there is a relatively critical weakness in OLED devices, that is, the organic light-emitting materials inside are extremely sensitive to water vapor and oxygen in the external environment. Once water vapor and oxygen invade the inside of the OLED device, chemical reactions will occur with the organic materials, resulting in problems such as reduced brightness, color deviation, and shortened lifespan. In severe cases, it may even cause the OLED device to fail and be unable to work properly in a short period of time. Therefore, in order to ensure the stable and reliable operation of the OLED device and achieve the expected service life and performance indicators, it is particularly important to effectively seal and protect it to form a reliable barrier to block the invasion of water vapor and oxygen.
[0004] In some existing solutions, (for example: application number: 202111609266.2, title: A preparation method of an OLED sealing solder), the preparation of the OLED sealing solder has the following steps: 1. Weigh the batch materials according to the molar percentage: 40-50% of Bi2O3, 5-15% of SiO2, 10-15% of B2O3, 15-25% of ZnO, 1-5% of Li2O, 1-5% of Na2O, 0-3% of SrO, 1-4% of BaO, 0-1.5% of MnO2, 2-5% of CuO, 0-5% of CeO2, 0-1.5% of Co2O3; 2. After completely mixing the above batch materials evenly, put them into a crucible and place it in a high-temperature furnace, heat it up to 800-1000°C at a rate of 1-10°C / min, keep it warm for 30-90 min, pour out the melted glass liquid and quench it rapidly to prepare the sealing glass; 3. Grind the prepared sealing glass to obtain a 50-200 μm sealing glass powder, and mix the organic binder with the sealing glass powder evenly according to the mass percentage of 10-20% to prepare the OLED sealing solder. However, the thermal expansion coefficients of the sealing solders with different ratios are all above 80×10 -7 / °C, and there is a large gap with the thermal expansion coefficient of the glass substrate (30-50×10 -7 / °C), which will affect the welding bonding force. Secondly, bubbles are likely to be generated during welding, which will affect the sealing performance. Summary of the Invention
[0005] One technical problem to be solved by this application is: the problems of poor sealing performance and weak welding bonding force of the encapsulation paste in the prior art.
[0006] To solve the above technical problems, the embodiments of this application provide a preparation method of an OLED sealing paste, and the method includes the following steps:
[0007] Step S10: Configure the first low melting point glass powder, and configure the first low melting point glass powder from the raw materials according to the molar percentage. Step S20: Configure the second low melting point glass powder, and configure the second low melting point glass powder from the raw materials according to the molar percentage. Step S30: Configure the composite powder, mix the first low melting point glass powder and the second low melting point glass powder to form a composite glass powder, and add a filler with a low thermal expansion coefficient and a light-absorbing filler to the composite glass powder to form a composite powder. Step S40: Configure the paste, and mix the composite powder and the organic carrier.
[0008] In some embodiments, when configuring the first low melting point glass powder, the following steps are further included:
[0009] Step S11: weigh the corresponding raw materials by mole percentage, 0.1 to 40% V2O5, 20 to 40% ZnO, 5 to 20% B2O3, 10 to 40% TeO2, 0 to 30% CuO, 0 to 10% SiO2, 0 to 10% BaO and 0 to 10% Bi2O3. Step S12: obtain the first low-melting glass powder, fully mix the raw materials, put them into a platinum crucible, heat and melt them in the temperature range of 1000 to 1300°C under the atmosphere, and keep them warm for 30min to 180min, then quench with water or metal to obtain glass slag, mechanically crush the glass slag, such as ball milling, sand milling or air flow milling, and process the glass slag into the first low-melting glass powder with a particle size Dmax less than 5um. Step S13: grouping, divide the first low-melting glass powder into five groups according to the different mole percentages of the raw materials, and record them as Y1, Y2, Y3, Y4 and Y5 respectively. Step S14: measuring the properties of the five groups of first low-melting-point glass powders, specifically measuring the glass transition temperature, softening temperature and thermal expansion coefficient.
[0010] In some embodiments, low expansion coefficient fillers and light absorbing fillers are added to five groups of first low-melting point glass powders to form five groups of first control composite powders, and the performance of the five groups of first control composite powders is measured, specifically the thermal expansion coefficient, water resistance, sintering density and bonding strength.
[0011] In some embodiments, when configuring the second low-melting-point glass powder, the following steps are also included:
[0012] Step S21: weigh the corresponding raw materials by mole percentage, 0.1 to 30% V2O5, 20 to 60% ZnO, 5 to 20% B2O3, 5 to 30% TeO2, 0 to 30% CuO, 0 to 15% SiO2, 0 to 10% BaO, 0 to 10% Bi2O3 and one or more of Fe2O3, MnO2, Nb2O5, Co3O4. Step S22: obtain a second low melting point glass powder, fully mix the raw materials, put them into a platinum crucible, heat and melt them in the temperature range of 1000 to 1300° C. under atmospheric atmosphere, and keep them warm for 30 min to 180 min, then quench with water or metal to obtain glass slag, and mechanically crush the glass slag, such as ball milling, sand milling or air flow milling, to process the glass slag into a second low melting point glass powder with a particle size Dmax less than 5 μm. Step S23: Grouping, according to the different molar percentages of the raw materials, the second low melting point glass powder is divided into five groups, respectively recorded as Y6, Y7, Y8, Y9 and Y10. Step S24: Determine the properties of the five groups of second low melting point glass powder, specifically, determine the glass transition temperature, softening temperature and thermal expansion coefficient.
[0013] In some embodiments, a filler with a low coefficient of thermal expansion and a light-absorbing filler are added to each of five groups of second low-melting-point glass powders to form five groups of second control composite powders, and the properties of the five groups of second control composite powders are measured, specifically, the coefficient of thermal expansion, water resistance, sintering densification, and bonding strength are measured.
[0014] In some embodiments, there are five groups of composite glass powders, and the five groups of composite glass powders are respectively formed by mixing first low-melting-point glass powders and second low-melting-point glass powders in different weight ratios, and the coefficients of thermal expansion of the five groups of composite glass powders are measured.
[0015] In some embodiments, a filler with a low coefficient of thermal expansion and a light-absorbing filler are added to five groups of composite glass powders to form five groups of composite powders, and the properties of the five groups of composite powders are measured, specifically, the coefficient of thermal expansion, water resistance, sintering densification, and bonding strength are measured.
[0016] In some embodiments, the glass transition temperature and the softening temperature are measured by a differential scanning calorimeter in a manner of heating at a heating rate of 10 °C / min up to a maximum of 700 °C; the coefficient of thermal expansion and the softening temperature are measured by a thermal analysis device in a manner of heating at a heating rate of 10 °C / min under a load of 0.05 N up to a maximum of 450 °C.
[0017] In some embodiments, the coefficient of thermal expansion is measured by a thermal analysis device in a manner of heating at a heating rate of 10 °C / min under a load of 0.05 N up to a maximum of 450 °C; the water resistance is measured by measuring the weight loss of the test piece after immersing the test piece in distilled water at 95 °C for 48 hours; the sintering densification is measured by measuring the maximum size and the number of bubbles in the cross-section at a magnification of 3000 times using a scanning electron microscope; the bonding strength is measured by a universal tensile testing machine.
[0018] In some embodiments, the composite powder and the organic carrier are mixed in a weight ratio within the range of 10:8 to 10:3 to form a slurry.
[0019] Through the above technical solution, the method for preparing the OLED sealing paste provided by the present application includes the following steps: configuring the first low melting point glass powder, configuring the second low melting point glass powder, configuring the composite powder, and configuring the paste. The first low melting point glass powder and the second low melting point glass powder are respectively configured from raw materials according to different molar percentages. Due to the difference in the ratio of raw materials, the glass transition temperature and the thermal expansion coefficient of the two will be different. After mixing the two, a composite glass powder is formed. A filler with a low expansion coefficient and a light-absorbing filler are added to the composite glass powder to form a composite powder. The thermal expansion coefficient of the composite powder is reduced and matches the thermal expansion coefficient of the glass substrate, thereby ensuring the welding bonding force. During the laser sealing process, there are fewer residual bubbles and excellent sealing performance. The technical solution of the present application effectively solves the problems of poor sealing performance and weak welding bonding force of the encapsulation paste in the prior art. Brief Description of the Drawings
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the following drawings are only some embodiments of the present application. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0021] Figure 1 It is a schematic flow chart of the method for preparing the OLED sealing paste in the embodiment of the present application;
[0022] Figure 2 It is a schematic flow chart of configuring the first low melting point glass powder in the embodiment of the present application;
[0023] Figure 3 It is a schematic flow chart of configuring the second low melting point glass powder in the embodiment of the present application. Detailed Embodiments
[0024] The following will further describe the embodiments of the present application in detail with reference to the drawings and embodiments. The detailed description and drawings of the following embodiments are used to exemplarily illustrate the principles of the present application, but cannot be used to limit the scope of the present application. The present application can be implemented in many different forms, not limited to the specific embodiments disclosed in the text, but including all technical solutions falling within the scope of the claims.
[0025] These embodiments of the present application are provided to make the present application thorough and complete, and to fully express the scope of the present application to those skilled in the art. It should be noted that: unless otherwise specifically stated, the relative arrangements of the components and steps described in these embodiments, the components of the materials, the numerical expressions and values should be interpreted as merely exemplary, rather than as limitations.
[0026] It should be noted that in the description of this application, unless otherwise specified, "a plurality of" means greater than or equal to two; the orientation or positional relationship indicated by terms such as "upper", "lower", "left", "right", "inner", "outer", etc. is only for the convenience of describing this application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be construed as a limitation to this application. When the absolute position of the object being described changes, the relative positional relationship may also change accordingly.
[0027] In addition, the "first", "second" and similar terms used in this application do not denote any order, quantity or importance, but are only used to distinguish different parts. "Vertical" is not strictly vertical, but within the allowable error range. "Parallel" is not strictly parallel, but within the allowable error range. Terms such as "comprising" or "including" mean that the elements before this term cover the elements listed after this term, and do not exclude the possibility of also covering other elements.
[0028] It should also be noted that in the description of this application, unless otherwise clearly specified and limited, the terms "installed", "connected" and "coupled" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be directly connected, or indirectly connected through an intermediate medium. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances. When it is described that a specific device is located between a first device and a second device, there may or may not be an intermediate device between the specific device and the first device or the second device.
[0029] All terms used in this application have the same meanings as those understood by ordinary skilled persons in the art to which this application pertains, unless otherwise specifically defined. It should also be understood that terms defined in a general dictionary, for example, should be interpreted as having meanings consistent with their meanings in the context of the relevant art, and should not be interpreted in an idealized or overly formal sense, unless specifically defined as such here.
[0030] Technologies, methods and devices known to those of ordinary skill in the relevant art may not be discussed in detail, but where appropriate, the technologies, methods and devices should be regarded as part of the specification.
[0031] Such as Figure 1As shown, the embodiment relates to a method for preparing an OLED sealing paste, comprising the following steps: Step S10: Prepare a first low-melting glass powder, and prepare the first low-melting glass powder from the raw materials according to a molar percentage. Step S20: Prepare a second low-melting glass powder, and prepare the second low-melting glass powder from the raw materials according to a molar percentage. Step S30: Prepare a composite powder, mix the first low-melting glass powder and the second low-melting glass powder to form a composite glass powder, and add a filler with a low expansion coefficient and a light-absorbing filler to the composite glass powder to form a composite powder. Step S40: Prepare a slurry, and mix the composite powder and the organic carrier.
[0032] Through the above technical scheme, the preparation method of the OLED sealing slurry provided in this embodiment includes the following steps: configuring a first low-melting point glass powder, configuring a second low-melting point glass powder, configuring a composite powder, and configuring a slurry. The raw materials are respectively configured to obtain a first low-melting point glass powder and a second low-melting point glass powder according to different molar percentages. Due to the difference in the ratio of the raw materials, the first low-melting point glass powder and the second low-melting point glass powder will have different glass transition temperatures and thermal expansion coefficients. The two are mixed to form a composite glass powder, and a filler with a low expansion coefficient and a light-absorbing filler are added to the composite glass powder to form a composite powder. The thermal expansion coefficient of the composite powder is reduced and matched with the thermal expansion coefficient of the glass substrate, thereby ensuring the welding bonding strength. During the laser sealing process, there are fewer residual bubbles and excellent sealing. The technical scheme of this embodiment effectively solves the problems of poor sealing and weak welding bonding strength of the encapsulation slurry in the prior art.
[0033] like Figure 2 As shown, in some embodiments, when configuring the first low-melting glass powder, the following steps are also included: Step S11: weigh the corresponding raw materials by mole percentage, 0.1 to 40% V2O5, 20 to 40% ZnO, 5 to 20% B2O3, 10 to 40% TeO2, 0 to 30% CuO, 0 to 10% SiO2, 0 to 10% BaO and 0 to 10% Bi2O3. Step S12: obtain the first low-melting glass powder, fully mix the raw materials, put them into a platinum crucible, heat and melt them in the temperature range of 1000 to 1300° C. under atmospheric atmosphere, and keep them warm for 30min to 180min, then water quench or metal quench to obtain glass slag, and mechanically crush the glass slag, such as ball milling, sand milling or air flow milling, to process the glass slag into the first low-melting glass powder with a particle size Dmax less than 5um. Step S13: Grouping, according to the different molar percentages of the raw materials, the first low melting point glass powder is divided into five groups, respectively denoted as Y1, Y2, Y3, Y4 and Y5. Step S14: Determine the properties of the five groups of first low melting point glass powders, specifically, determine the glass transition temperature, softening temperature and thermal expansion coefficient.
[0034] The functions of the above raw material components are described as follows:
[0035] V2O5: It can enhance the absorption ability of laser, has the functions of a glass former and low melting point characteristics. At the same time, V2O5 can improve the flow characteristics and play the role of a flux in reducing the glass transition temperature.
[0036] ZnO: It is beneficial to improve the water resistance to ensure the stability of the glass, and can also be used to improve the flow characteristics, reduce the thermal expansion coefficient, lower the softening temperature, and inhibit devitrification.
[0037] B2O3: As a glass-forming substance, it can inhibit the sharp increase in the viscosity of the glass.
[0038] TeO2: It can form glass, enhance the bonding force of the glass, thereby ensuring water resistance and chemical resistance, and play the role of a flux in reducing the glass transition temperature.
[0039] CuO: It is used to increase the infrared absorption rate.
[0040] SiO2: Together with B2O3, it undertakes the role of a glass-forming substance and can reduce the thermal expansion coefficient.
[0041] BaO: It is a network-modifying former and, as a flux for reducing the glass transition temperature, plays the role of improving the stabilization of the glass and preventing devitrification.
[0042] Bi2O3: It is used to adjust the thermal expansion coefficient. As a network modifier, it is beneficial to improve the stability of the glass.
[0043] The specific raw materials of the five groups of the first low melting point glass powder are shown in Table 1 below.
[0044] Table 1 Specific raw materials of the five groups of the first low melting point glass powder (unit: mole percentage)
[0045]
[0046] In some embodiments, a low expansion coefficient filler and a light-absorbing filler are added to the five groups of the first low melting point glass powder to form five groups of first control composite powders, and the properties of the five groups of first control composite powders are measured, specifically the thermal expansion coefficient, water resistance, sintering denseness, and bonding force are measured.
[0047] It should be noted that the low expansion coefficient filler can be selected from one or a combination of more of nepheline syenite, cordierite, zirconium phosphate, zirconium tungstate, zirconium phosphotungstate, zirconium vanadate, tridymite, and cristobalite. The light-absorbing filler can be selected from one or a combination of more of iron manganate and copper chromite. In this embodiment, the low expansion coefficient filler is zirconium tungstate, and the light-absorbing filler is copper chromite.
[0048] The specific properties of the five groups of first low-melting-point glass powders and the corresponding five groups of first control composite powders are shown in Table 2 below:
[0049] Table 2 Properties of the first low melting point glass powder and the first control composite powder
[0050]
[0051] Referring to Table 2, it can be seen that the glass transition temperature of the first low melting point glass powder is below 350°C and the thermal expansion coefficient is 60×10 -7 / ℃ or above.
[0052] like Figure 3 As shown, in some embodiments, when configuring the second low-melting glass powder, the following steps are also included: Step S21: weigh the corresponding raw materials by mole percentage, 0.1 to 30% V2O5, 20 to 60% ZnO, 5 to 20% B2O3, 5 to 30% TeO2, 0 to 30% CuO, 0 to 15% SiO2, 0 to 10% BaO, 0 to 10% Bi2O3 and one or more of Fe2O3, MnO2, Nb2O5, Co3O4. Step S22: obtain the second low-melting glass powder, fully mix the raw materials, put them into a platinum crucible, heat and melt them in the temperature range of 1000 to 1300°C under atmospheric atmosphere, and keep them warm for 30min to 180min, then quench with water or metal to obtain glass slag, and mechanically crush the glass slag, such as ball milling, sand milling or air flow milling, to process the glass slag into the second low-melting glass powder with a particle size Dmax less than 5um. Step S23: Grouping, according to the different molar percentages of the raw materials, the second low melting point glass powder is divided into five groups, respectively recorded as Y6, Y7, Y8, Y9 and Y10. Step S24: Determine the properties of the five groups of second low melting point glass powder, specifically, determine the glass transition temperature, softening temperature and thermal expansion coefficient.
[0053] The functions of the above raw materials are described as follows:
[0054] V2O5: It can enhance the absorption of laser light, and has the function of glass former and low melting point. At the same time, V2O5 can improve the flow characteristics and play the role of flux to reduce the glass transition temperature.
[0055] ZnO: It helps to improve water resistance to ensure the stability of glass. It can also be used to improve flow characteristics, reduce the coefficient of thermal expansion, lower the softening temperature, and inhibit devitrification.
[0056] B2O3: As a glass-forming substance, it can suppress the rapid increase of glass viscosity.
[0057] TeO2: It can form glass, enhance the bonding strength of the glass, thereby ensuring water resistance and chemical resistance, and acting as a flux to reduce the glass transition temperature.
[0058] CuO, Fe2O3, MnO2, Nb2O5, Co3O4: Used to increase the infrared absorption rate.
[0059] SiO2: Together with B2O3, it acts as a glass-forming substance and can reduce the thermal expansion coefficient.
[0060] BaO: It is a network modifier and acts as a flux to reduce the glass transition temperature, playing a role in improving the glass stability and preventing devitrification.
[0061] Bi2O3: Used to adjust the thermal expansion coefficient. As a network modifier, it is beneficial to improve the glass stability.
[0062] The specific raw materials of the five groups of second low-melting-point glass powders are shown in Table 3 below.
[0063] Table 3 Specific raw materials of the five groups of second low-melting-point glass powders (unit: mole percentage)
[0064]
[0065] In some embodiments, fillers with low thermal expansion coefficients and light-absorbing fillers are added to the five groups of second low-melting-point glass powders to form five groups of second control composite powders, and the properties of the five groups of second control composite powders are measured, specifically the thermal expansion coefficient, water resistance, sintering density, and bonding strength.
[0066] It should be noted that the fillers with low thermal expansion coefficients can be selected from one or more combinations of lithium nepheline, cordierite, zirconium phosphate, zirconium tungstate, zirconium phosphotungstate, zirconium vanadate, tridymite, and cristobalite. The light-absorbing fillers can be selected from one or more combinations of iron manganate and copper chromite. In this embodiment, the filler with a low thermal expansion coefficient is zirconium tungstate, and the light-absorbing filler is copper chromite.
[0067] The specific properties of the five groups of second low-melting-point glass powders and their corresponding five groups of second control composite powders are shown in Table 4 below:
[0068] Table 4 Properties of the second low-melting-point glass powders and the second control composite powders
[0069]
[0070] Referring to Table 4, it can be seen that the glass transition temperature of the second low-melting-point glass powders is above 350 °C, and the thermal expansion coefficient is at 60×10 -7Below / ℃. The reason for the difference compared with the first low-melting-point glass powder is that the glass transition temperature and the thermal expansion coefficient affect each other in some aspects. When the glass transition temperature is higher, the glass structure is more stable and the thermal expansion coefficient becomes lower. On the contrary, when the glass transition temperature is lower, the glass structure becomes looser and the thermal expansion coefficient becomes higher.
[0071] For the first low-melting-point glass powders Y1 - Y5, the bubble size is relatively large. Due to the relatively low glass transition temperature, it may lead to better fluidity and lower viscosity of the glass melt during the laser process, resulting in the gathering of bubbles together during the laser process and forming through-bubbles. For the second low-melting-point glass powders Y6 - Y10, the bubble size is slightly larger and the number of bubbles is relatively large. This may be due to the relatively high glass transition temperature, resulting in more small bubbles generated during the pre-sintering process. During the laser process, these small bubbles expand into large bubbles. The degree of bubbles after laser will have a certain impact on the sealing performance of the encapsulation paste.
[0072] In some embodiments, there are five groups of composite glass powders. The five groups of composite glass powders are respectively mixed by the first low-melting-point glass powder and the second low-melting-point glass powder with different weight ratios, and the thermal expansion coefficients of the five groups of composite glass powders are measured. Low-expansion fillers and light-absorbing fillers are added to the five groups of composite glass powders to form five groups of composite powders. Relative to 100 parts by weight of the composite powder, it contains less than 50 parts by weight of low-expansion fillers (low-expansion crystalline ceramic fillers), and relative to 100 parts by weight of the composite powder, it contains less than 20 parts by weight of light-absorbing fillers. And the properties of the five groups of composite powders are measured, specifically, the thermal expansion coefficient, water resistance, sintering densification, and bonding strength are measured. It should be noted that the low-expansion filler can be selected from one or more combinations of lithium nepheline, cordierite, zirconium phosphate, zirconium tungstate, zirconium phosphotungstate, zirconium vanadate, tridymite, and cristobalite. The light-absorbing filler can be selected from one or more combinations of iron manganate and copper chromite. In this embodiment, the low-expansion filler is zirconium tungstate and the light-absorbing filler is copper chromite. In this embodiment, the weight ratio of the composite glass powder, the low-expansion filler, and the light-absorbing filler is 36:3:1.
[0073] The specific properties of the five groups of composite glass powders and their corresponding five groups of composite powders are shown in Table 5 below:
[0074] Table 5 Properties of Composite Glass Powders and Composite Powders
[0075]
[0076] Referring to Table 5, it can be seen that after mixing the first low-melting-point glass powder and the second low-melting-point glass powder in a certain proportion, the thermal expansion coefficients are all around 60×10 -7 / ℃. After adding the mixed low-expansion fillers and light-absorbing fillers, the thermal expansion coefficient is further reduced to 47×10 -7around / ℃, which matches the thermal expansion coefficient of the glass substrate of 30 - 50×10 -7 / ℃, ensuring more reliable welding bonding force.
[0077] By comparing the maximum pore diameter and the number of pores of the first control composite powder and the second control composite powder, it can be seen that the maximum pore diameter of the composite powder is smaller and the number of pores is fewer. This is because after mixing the first low-melting-point glass powder and the second low-melting-point glass powder, during the pre-sintering process, the first low-melting-point glass powder has a low softening point and melts first, then wets and wraps the second low-melting-point glass powder, the low-expansion coefficient filler, and the light-absorbing filler, fully discharging the bubbles remaining from the volatilization of the organic solvent and filling the pores generated by the volatilization of the organic solvent, making the sintering more densified. At this time, the second low-melting-point glass powder, the low-expansion coefficient filler, and the light-absorbing filler do not melt and play a supporting role to prevent the first low-melting-point glass powder from flowing to other positions. As the temperature further increases, the second low-melting-point glass powder begins to melt, and the first low-melting-point glass powder and the second low-melting-point glass powder are fully mixed. Moreover, the second low-melting-point glass powder has better light absorption, making the light absorption more uniform and avoiding the situation of generating large bubbles due to strong local light absorption ability. At the same time, since P2O5 with poor water resistance is not added, the water resistance is better.
[0078] In some embodiments, the glass transition temperature and the softening temperature are measured by a differential scanning calorimeter in a manner of heating at a heating rate of 10℃ / min up to a maximum of 700℃; the thermal expansion coefficient and the softening temperature are measured by a thermal analysis device in a manner of heating at a heating rate of 10℃ / min up to a maximum of 450℃ under a load of 0.05N.
[0079] In some embodiments, the thermal expansion coefficient is measured by a thermal analysis device in a manner of heating at a heating rate of 10℃ / min up to a maximum of 450℃ under a load of 0.05N; the water resistance is measured by measuring the weight loss of the test piece after immersing the test piece in distilled water at 95℃ for 48 hours, and the test piece is the corresponding first control composite powder test piece and the second control composite powder test piece; the sintering densification is measured by using a scanning electron microscope to measure the maximum size and the number of bubbles in the cross-section at a magnification of 3000 times; the bonding force is measured by a universal tensile testing machine.
[0080] In some embodiments, the composite powder and the organic carrier are mixed in a weight ratio ranging from 10:8 to 10:3 to form a slurry. In this embodiment, the composite powder and the organic carrier are prepared in a weight ratio of 7:3. The organic carrier mainly contains high-boiling organic substances and / or binders. The main function of the organic carrier is to adjust the viscosity and thixotropy of the slurry, so that the slurry can be stored stably and fine silk-screened circuits can be obtained during the printing process. Finally, a slurry with appropriate viscosity and fineness <5 μm is prepared. The slurry is printed on the bottom glass sheet, and then dried at 150 °C for 30 min to dry most of the organic solvents in the slurry, and then pre-sintered at 430 °C for 30 min. The glass cover plate is placed on the pre-sintered glass glue, and the glass sealing ring is irradiated with laser from one side of the glass cover plate. The glass sealing ring absorbs the laser energy and is melted and welded to the glass substrate and the glass cover plate. The cross-sectional bubble condition is observed with a scanning electron microscope, and the universal tensile testing machine is used to vertically stretch until the glass sheet breaks and separates to test its tensile strength.
[0081] So far, the embodiments of the present application have been described in detail. To avoid obscuring the concept of the present application, some details known in the art are not described. Those skilled in the art can fully understand how to implement the technical solutions disclosed herein based on the above description.
[0082] Although some specific embodiments of the present application have been described in detail by way of examples, those skilled in the art should understand that the above examples are only for illustration and not for limiting the scope of the present application. Those skilled in the art should understand that the above embodiments can be modified or some technical features can be equivalently replaced without departing from the scope and spirit of the present application. In particular, as long as there is no structural conflict, the technical features mentioned in each embodiment can be combined in any way.
Claims
1. A preparation method of an OLED sealing paste, characterized in that The following steps are involved: Step S10: preparing a first low-melting-point glass powder by preparing the raw materials according to molar percentage; Step S20: preparing a second low melting point glass powder by preparing the raw materials according to molar percentage to obtain the second low melting point glass powder; Step S30: preparing a composite powder, mixing the first low-melting point glass powder and the second low-melting point glass powder to form a composite glass powder, and adding a filler with a low expansion coefficient and a light-absorbing filler to the composite glass powder to form a composite powder; Step S40: preparing slurry by mixing the composite powder and the organic carrier.
2. The preparation method of the OLED encapsulation paste according to claim 1, characterized in that, When configuring the first low-melting-point glass powder, the following steps are also included: Step S11: weighing the corresponding raw materials by mole percentage, 0.1 to 40% of V2O5, 20 to 40% of ZnO, 5 to 20% of B2O3, 10 to 40% of TeO2, 0 to 30% of CuO, 0 to 10% of SiO2, 0 to 10% of BaO and 0 to 10% of Bi2O3; Step S12: obtaining a first low-melting-point glass powder, fully mixing the raw materials, loading them into a platinum crucible, heating and melting them in an atmospheric atmosphere within a temperature range of 1000 to 1300° C., and keeping the temperature for 30 to 180 minutes, then quenching with water or metal to obtain glass slag, and mechanically crushing the glass slag, such as by ball milling, sand milling or air flow milling, to process the glass slag into a first low-melting-point glass powder with a particle size Dmax less than 5 μm; Step S13: grouping, dividing the first low-melting-point glass powder into five groups according to different molar percentages of various raw materials, respectively denoted as Y1, Y2, Y3, Y4 and Y5; Step S14: measuring the properties of the five groups of the first low-melting-point glass powders, specifically measuring the glass transition temperature, softening temperature and thermal expansion coefficient.
3. The preparation method of the OLED encapsulation paste according to claim 2, wherein, Fillers with low expansion coefficients and light-absorbing fillers were added to the five groups of the first low-melting point glass powders to form five groups of first control composite powders, and the properties of the five groups of the first control composite powders were measured, specifically the thermal expansion coefficient, water resistance, sintering density and bonding strength.
4. The preparation method of the OLED encapsulation paste according to claim 1, characterized in that, When preparing the second low-melting-point glass powder, the following steps are also included: Step S21: weighing the corresponding raw materials by mole percentage, 0.1 to 30% of V2O5, 20 to 60% of ZnO, 5 to 20% of B2O3, 5 to 30% of TeO2, 0 to 30% of CuO, 0 to 15% of SiO2, 0 to 10% of BaO, 0 to 10% of Bi2O3 and one or more of Fe2O3, MnO2, Nb2O5, Co3O4; Step S22: obtaining a second low melting point glass powder, fully mixing the raw materials, loading into a platinum crucible, heating and melting in an atmospheric atmosphere within a temperature range of 1000 to 1300° C., and keeping the temperature for 30 to 180 minutes, then quenching with water or metal to obtain glass slag, and mechanically crushing the glass slag, such as by ball milling, sand milling or air flow milling, to process the glass slag into a second low melting point glass powder with a particle size Dmax less than 5 μm; Step S23: Grouping. The second low-melting-point glass powder is divided into five groups according to different molar percentages of each raw material, and is denoted as Y6, Y7, Y8, Y9, and Y10 respectively; Step S24: Measuring the properties of the five groups of the second low-melting-point glass powder, specifically measuring the glass transition temperature, softening temperature, and coefficient of thermal expansion.
5. The preparation method of the OLED encapsulation paste according to claim 4, characterized in that, Add a filler with a low coefficient of thermal expansion and a light-absorbing filler to the five groups of the second low-melting-point glass powder to form five groups of second control composite powders, and measure the properties of the five groups of the second control composite powders, specifically measuring the coefficient of thermal expansion, water resistance, sintering density, and bonding strength.
6. The preparation method of the OLED encapsulation paste according to claim 1, wherein There are five groups of the composite glass powder, and the five groups of the composite glass powder are respectively mixed by the first low-melting-point glass powder and the second low-melting-point glass powder with different weight ratios, and the coefficient of thermal expansion of the five groups of the composite glass powder is measured.
7. The preparation method of the OLED encapsulation paste according to claim 6, wherein, Add a filler with a low coefficient of thermal expansion and a light-absorbing filler to the five groups of the composite glass powder to form five groups of composite powders, and measure the properties of the five groups of the composite powders, specifically measuring the coefficient of thermal expansion, water resistance, sintering density, and bonding strength.
8. The preparation method of the OLED encapsulation paste according to claim 2 or 4, characterized in that, The glass transition temperature and the softening temperature are measured by a differential scanning calorimeter in a manner of heating at a heating rate of 10 °C / min until the maximum temperature of 700 °C; the coefficient of thermal expansion and the softening temperature are measured by a thermal analysis device in a manner of heating at a heating rate of 10 °C / min under a load of 0.05 N until the maximum temperature of 450 °C.
9. The preparation method of the OLED encapsulation paste according to claim 3 or 5, characterized in that, The coefficient of thermal expansion is measured by a thermal analysis device in a manner of heating at a heating rate of 10 °C / min under a load of 0.05 N until the maximum temperature of 450 °C; the water resistance is measured by measuring the weight loss of the test piece after immersing the test piece in distilled water at 95 °C for 48 hours; the sintering density is measured by using a scanning electron microscope to measure the maximum size and the number of bubbles in the cross section at a magnification of 3000 times; the bonding strength is measured by a universal tensile testing machine.
10. The preparation method of the OLED encapsulation paste according to claim 1, wherein, Mix the composite powder and the organic carrier in a weight ratio within the range of 10:8 to 10:3 to form a slurry.
Citation Information
Patent Citations
Preparation method of solder suitable for OLED (Organic Light Emitting Diode) sealing
CN114212995A